2018
DOI: 10.1016/j.cell.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Parvovirus Drives Chronic Tubulointerstitial Nephropathy and Kidney Fibrosis

Abstract: The occurrence of a spontaneous nephropathy with intranuclear inclusions in laboratory mice has puzzled pathologists for over 4 decades, because its etiology remains elusive. The condition is more severe in immunodeficient animals, suggesting an infectious cause. Using metagenomics, we identify the causative agent as an atypical virus, termed "mouse kidney parvovirus" (MKPV), belonging to a divergent genus of Parvoviridae. MKPV was identified in animal facilities in Australia and North America, is transmitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
181
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(196 citation statements)
references
References 60 publications
6
181
2
Order By: Relevance
“…For example, ambidensovirus-derived EPVs dominate invertebrate genomes (14), whereas vertebrate EPVs almost exclusively derive from dependoparvoviruses, protoparvoviruses, or viruses closely related to these two genera (12, 13, 25, 26). In this study we found no trace of ChPV-derived sequences in tetrapod genomes, despite recent evidence that ChPVs infect this host group (21). By contrast, ChPV-derived sequences are relatively common in arthropods, with the genomes of some species harboring multiple, independently acquired ChPVs ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…For example, ambidensovirus-derived EPVs dominate invertebrate genomes (14), whereas vertebrate EPVs almost exclusively derive from dependoparvoviruses, protoparvoviruses, or viruses closely related to these two genera (12, 13, 25, 26). In this study we found no trace of ChPV-derived sequences in tetrapod genomes, despite recent evidence that ChPVs infect this host group (21). By contrast, ChPV-derived sequences are relatively common in arthropods, with the genomes of some species harboring multiple, independently acquired ChPVs ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 94%
“…Our discovery of ChPV-derived elements in fish and arthropod genomes establishes that ChPVs can infect these species in addition to mammals (21). Moreover, it provides evidence that the ChPVs are probably an ancient lineage of parvoviruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Shelduck parvovirus described here is of particular interest as it is a member of the genus Chapparvovirus. Metagenomic analyses have recently identified members of this genus in a large number of vertebrates [55], and are known agents of severe disease [56].…”
Section: Discussionmentioning
confidence: 99%
“…Chapparvoviruses are being increasingly identified in metagenomic studies, and seemingly have a wide host range (42), including bats (43), and the feces of turkeys (44), red-crowned cranes (45), wild rats (46) and pigs (47). Importantly, a murine kidney parvovirus was recently found in immunodeficient laboratory mice strains, causing renal failure and kidney fibrosis (48), indicating that some chapparvoviruses are associated with highly virulent infections.…”
Section: Discussionmentioning
confidence: 99%